Küreselleşmenin Medya Üzerinde Etkileri: Küresel Medyaya “Sürükleniş” / The Effects of Globalization on Media: "Drifting" into the Global Media - Kasap, Fevzi; Dolunay, Ayhan; Mırçık, Ali Murat (Journal of History Culture and Art Research, 2018)
Abstract Globalization affects the lives of individuals by showing themselves in many areas. The notion of globalization, which is particularly influential in the field of economy, politics and culture, has led to change and transformation through important influences both in the media and in the news cycle. In this context, with the globalization of the media, attempts have been made to create a uniform culture all over the world. Movies, TV programs, music video clips, have also changed in support of this argument. The global news cycle, which is in the hands of international agencies, causes an imbalance in the global flow as it is published due to the views of western imperialism of a certain capital. In this context, "news" is only in the hands of certain agencies; the dominance is maintained. In particular, although they are working to correct them on the effects of the global media and on the imbalances in the news cycle, they have not yet reached a sufficient level. Because of the international cycle of communication, the global media environment is in the hands of certain capitalists, imbalances are also felt in the environment. In this study, it will be discussed how the globalization phenomenon, especially the reflection of the media, and as a result, the news and other visual media messages affect the target audience. Following the identification of the situation, this structure will be referred to the work that can be described as "contradictions" and this particular emphasis on local / new media actors that may create alternatives will be addressed. Öz Küreselleşme, pek çok alanda kendini göstererek, bireylerin yaşamlarını etkilemektedir. Özellikle ekonomi, siyaset ve kültür alanında etkili olan küreselleşme kavramı, medyada ve haber döngüsünde de önemli etkileri vasıtasıyla değişim ve dönüşüme yol açmıştır. Buna kapsamda, medyanın küreselleşmesiyle birlikte, tüm dünya üzerinde tek tip bir kültür oluşturulması girişimleri de söz konusu olmuştur. Filmler, tv programları, müzik klipleri de bu savı destekler nitelikte değişimler göstermiştir. Uluslararası ajansların elinde olan küresel haber döngüsü ise belli bir sermayeye ait batı emperyalizmi görüşlerine bağlı olarak yayınlandığı için küresel akışta bir dengesizliğe sebep olmaktadır. Bu kapsamda, “haber” sadece belli ajansların elinde olup; söz konusu hakimiyet sürdürülmektedir. Özellikle, küresel medyanın etkilerinde ve haber döngüsündeki dengesizlikler üzerinde bunları düzeltmeye yönelik çalışmalar olsa da, henüz yeterli düzeye erişilememiştir. İletişimdeki uluslararası döngü, küresel medya ortamı belli sermayelerin elinde olduğu için ortamda dengesizlikler de kendini hissettirmektedir. Bu çalışmada küreselleşme olgusunun özellikle medyaya yansımaları ve bunun sonucunda haberlerin ve diğer görsel medya iletilerinin hedef kitleyi nasıl etkileyip, yönlendirdiği tartışılacak; durum tespiti ardından, bu yapıya “karşı çıkışlar” olarak nitelenebilecek çalışmalara değinilecek ve alternatif oluşturabilecek yerel/yeni medya aktörlerinin bu husustaki önemi ele alınacaktır.